Students’ Perceptions of Teacher-Designed Interactive Canva AI Materials in Developing English Skills - Afriliana, Fina; Zamzam, Ahmad; Putera, Lalu Jaswadi (Journal of Authentic Research, 2026)
Students still face challenges in understanding English learning materials, especially descriptive texts. The lack of interactive digital media is one of the causes of low student engagement and understanding, resulting in less than optimal learning outcomes. This study aims to determine students' perceptions of Canva-based interactive materials designed by teachers in learning descriptive texts. This study used a qualitative descriptive design supported by quantitative data. The subjects of this study were 32 10th-grade students selected using a total sampling technique. Data collection was conducted through a Likert-scale questionnaire and semi-structured interviews. The results showed that most students had a positive perception of the use of Canva materials, with details of 56.3% in the positive category, 28.1% neutral, and 15.6% negative. These findings indicate that the majority of students perceive the benefits of using Canva in learning, such as increased engagement, motivation, and understanding of the material, although a small number of students still face technical difficulties. Practically, these findings provide implications for English teachers are advised to integrate Canva's interactive features such as quizzes with immediate feedback, color-coded activities, and sentence construction exercises into their learning designs. Teachers also need to consider the availability of technological infrastructure, such as providing offline materials or ensuring a stable internet connection, and designing materials with a gradual level of difficulty to accommodate diverse student abilities. Thus, Canva serves not only as a visual presentation tool but also as a student-centered, interactive learning environment.